THE CORRELATION OF FUNCTIONAL DISABILITY INDEXES WITH DISEASE ACTIVITY DETERMINANTS IN WOMEN WITH ACUTE RHEUMATOID ARTHRITIS - Murat Birtane,; Aral Hakgüder,; Merih Eryavuz,; Siranuş Kokino, (Archives of Rheumatology, 2001)
Rheumatoid arthritis (RA) is a chronic inflammatory disease causing joint deformities and consequent functional disability. The aim of this cross-sectional study was to assess the possible correlations between some determinants of disease activity such as Ritchie articular index (RAI), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and the functional disability questionnaires in women with acute RA, aged between 50 and 65. The functional status of 52 women with acute RA, diagnosed according to modified ARA criteria were assessed by Health Assessment Questionnaire (HAQ) and Lee Functional Index (LFI). Ritchie Articular Index values were determined with joint examination, ESR and CRP with laboratory techniques in blood samples. The relations between these disease activity determinants and functional scores were assessed by correlation analysis. A strong positive correlation was found between two functional indexes (r= 0.84, p < 0.0001). The significant correlations found between ESR, CRP and LFI ( r=0.33, p < 0.01; r=0.44, p < 0.001, respectively), were stronger than the positive correlations determined between the same variables and HAQ (r=0.25, p<0.05; r=0.30, p<0.05, respectively). RAI exhibited stronger correlations with HAQ and LFI when compared with those of laboratory variables with HAQ (r=0.49, p<0.01; r= 0.59, p< 0.001, respectively). The most related disease activity determinants with examined functional disability levels in women with acute RA were observed to be RAI, CRP and ESH, consecutively. The prediction values of joint symptoms seemed to be more prominent when compared with laboratory variables.